Development Of Oral Wound Healing Formulation From Ocimum Tenuiflorum Extract - Jayaraman, Rohini (2020)
The research aims to develop a wound healing formulation to improve the efficacy of the plant Ocimum tenuiflorum extract. The study consists of 4 phases of analysis whereby in phase 1, the plant was evaluated for wound healing potential using three different parts (leaves, stems, and flowers) of aqueous extract on in vitro wound healing assays.